Agreement among the energy expenditure prediction equations with the criterion model in the exhaustive treadmill test protocols - معرفت سیاه کوهیان; الهه ممشلی (Shahid Beheshti University, 2016)
Purpose: The aim of this study was to survey the agreements between the energy expenditure prediction equations withthe criterion model in the exhaustive treadmill test protocols in active young men. Methods:Fifty active young men wereselected as subjects (Mean ± SD Age 21.04 ± 2.069 yrs., Height 176.78 ± 4.484 cm, Weight 70.11 ± 5.825kg) andcompleted exhaustive treadmill test protocols. Bioenergetical variables during exhaustive protocols using respiratory gasanalysis were collected at an interval of ten seconds. To estimate the energy cost and bioenergetical variables,ACSMv,Vander Walt, Pandolf, Léger and Epstein predictive equations for walking and running were considered. Bland-Altmangraphical model and Interclass Correlation Coefficient (ICC) statistical tests were used to evaluate the absolute agreementof the methods. Results:The results suggest that the Leger equation for running have high agreement with the criterionmodel (±1.96; CI = 95% -21.2 to 2.4 ml/kg/min; ICC= 0.89)And ACSM walking and running equations have middleagreementwith the criterion model(Walking: ±1.96 ; 95% CI = -8.1to +4.7ml/kg/min,ICC= 0.4837;Running: ±1.96 ; 95%CI = -27.6 to -3.3 ml/kg/min, ICC: 0.4535). Conclusions: According to study results it could be concluded that the Legerequations for running and relativelyACSM walking and running equations estimating of VO2 among Iranian active youngmen can be used as an accurate alternative for the criterion method.